Public pedagogies of edible verge gardens: Cultivating streetscapes of care. Issue 7 (October 2019) - Hsu, Jesse P
Edible verge gardens, which are cultivated sections of public footpaths created by residents for household and community use, have gradually become more common in some Australian cities. As an emergent form of urban agriculture, verge gardens uniquely provide opportunities for encountering and learning about food cultivation and consumption practices at the mundane level of the footpath. The "public pedagogy" potentially generated by the spaces can be conceptualized as not only a range of garden-oriented learning experiences but also an incremental journey of embedding into the daily life of the neighborhood. Considering this 'pedagogical life' enables understanding of the extent to which specific urban agricuture spaces mediate care, or the interdependence between all human and non-human life, in the function-oriented spaces of the city. To this end, I explore the interplay of semiotic and performative aspects of verge gardens through multimodal discourse analysis and ethnographic methods, respectively, to understand both the material affordances present in and through the spaces as well as the subsequent "post-launch" life of the gardens. This 'multimodal-performative' approach allows for a micro-scale understanding of how urban agriculture spaces potentially re-educate public sensibilities around food and reimagine the city in terms of care—a visible integration of food, community, and urban space. The analysis elucidates the mundane yet consequential process of urban agriculture spaces folding into the everyday rhythms of neighborhood life. This research suggests that the ethics of everyday food practices (i.e. cultivation, procurement, preparation, eating, etc.) and the ethics of space are intimately related.